Case Report: Hypercalcemia as a manifestation of acute adrenal crisis precipitated by fluconazole use, and a review of the literature - Choo, Kuan Swen; Yew, Jielin; Tan, Eberta Jun Hui; Puar, Troy Hai Kiat (Frontiers in Endocrinology, 2023)
Acute adrenal crisis classically presents with vomiting, altered sensorium and hypotension. We describe a unique case manifesting with severe hypercalcemia. Addisonian crisis was unusually precipitated by fluconazole use. We reviewed other reported cases and discuss possible mechanisms of hypercalcemia in adrenal insufficiency. This 67-year-old man presented with fever, cough and vomiting for one week, and anorexia and confusion for three weeks. He was hypotensive and clinically dehydrated. Investigations revealed left-sided lung consolidation, acute renal failure and severe non-Parathyroid hormone-mediated hypercalcemia (calcium 3.55mol/L; PTH 0.81pmol/L). Initial impression was pneumonia complicated by septic shock, and hypercalcemia secondary to possible malignancy. He received mechanical ventilation, treatment with intravenous fluids, inotropes, and hydrocortisone for septic shock, and continuous renal replacement therapy with low-calcium dialysate. While hypercalcemia resolved and he was weaned off inotropes, dialysis, and hydrocortisone, his confusion persisted. When hypercalcemia recurred on Day 19 of admission, early-morning cortisol was <8nmol/L, with low ACTH level (3.2ng/L). Other pituitary hormones were normal. Hypercalcemia resolved three days after reinstating stress doses of hydrocortisone, and his mentation normalized. On further questioning, he recently received fluconazole for a forearm abscess. He previously consumed traditional medications but stopped several years ago, which may have contained glucocorticoids. He was discharged on oral hydrocortisone. Cortisol levels improved gradually, and glucocorticoid replacement was ceased after eight years, without any recurrence of hypercalcemia or Addisonian crisis. Both hypercalcemia and adrenal insufficiency may present with similar non-specific symptoms. It is important to consider adrenal insufficiency in hypercalcemia of unclear etiology.